The Effect of A Training Program Using Higher-order Thinking Skills on Creative and Critical Thinking Among A Sample of Basic Tenth-Grader Students - Ashour, Mohamad (Jordan Journal of Educational Sciences, 2005)
This study aimed at clarifying the role of secondary school principals in improving the relationship between school and the community. This study tried to answer the following questions: (1) What is the role of secondary school principal in improving the relationship between school and the community? (2) What are the secondary school principals’ priorities in improving the relationship between school and the community? The population of this study consisted of (454) secondary school principals in Irbid Governorate, and a randomly selected sample of (200) principals was selected, which represented (43.9%) of the total population. To achieve the aims of this study, the researcher developed a questionnaire after assuring its validity and reliability; this questionnaire included (57) items, distributed into seven categories as follows: cultural cooperation with the community, benefiting from the local community resources, continuing education programs for the community, providing human and social services for the community, school participation in providing certain services, and encouraging parents and school teachers to provide school services to the community. Based on the result the researcher recommends the following:(1) Directing secondary school principals to the Ministry of Education’s rules and regulations, which allow improving the relationship between school and the community. (2) More delegation of authority is needed for secondary school principals to improve the relationship with the community. (3) More attention to the activities is needed to improve the relationship between school and the community.